Reducing tensions between Russia and NATO - Marten, Kimberly Zisk, 1963- (CSR (New York, N.Y.), 2017)
"Outlines how U.S. policymakers can deter Russian aggression with robust support for NATO, while reassuring Russia of NATO's defensive intentions through clear words and actions based in international law. Marten ... lays out several scenarios that could lead to a dangerous confrontation, ranging from an inadvertent encounter between NATO and Russian military aircraft or ships to an intentional Russian land grab in Europe. The report ... offers a plan for how the Donald J. Trump administration could work with Congress and NATO allies to lessen the chances of crisis escalation"--Publisher's web site.